2018
DOI: 10.3892/ijmm.2018.3430
|View full text |Cite
|
Sign up to set email alerts
|

Aberrantly expressed long noncoding RNAs in hypertrophic scar fibroblasts in vitro: A microarray study

Abstract: A hypertrophic scar is the result of abnormal repair of the body after trauma. Histopathologically, it is mostly the result of the excessive proliferation of fibroblasts and the accumulation of extracellular matrix. Accumulating evidence has demonstrated that long non-coding RNAs (lncRNAs) have a critical role in the regulation of gene expression and in the pathogenesis of diseases. However, the roles of lncRNAs in hypertrophic scars have remained elusive. The present study investigated the profiles of differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 44 publications
1
34
0
Order By: Relevance
“…The mean CT values of MIR‐206 in the three groups were 22.33, 20.95, and 20.11, respectively. According to the formula for calculating the relative expression of each sample, as far as the relative expression of mTOR is concerned, cells without laser irradiation showed the highest expression, cells irradiated by high‐energy laser had the lowest expression (0.56), and the expression in cells irradiated by low‐energy laser was 0.83 (Figure B). In contrast, the relative expression of miR‐206 was the lowest in non‐laser irradiated samples .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The mean CT values of MIR‐206 in the three groups were 22.33, 20.95, and 20.11, respectively. According to the formula for calculating the relative expression of each sample, as far as the relative expression of mTOR is concerned, cells without laser irradiation showed the highest expression, cells irradiated by high‐energy laser had the lowest expression (0.56), and the expression in cells irradiated by low‐energy laser was 0.83 (Figure B). In contrast, the relative expression of miR‐206 was the lowest in non‐laser irradiated samples .…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the relative expression of miR-206 was the lowest in non-laser irradiated samples. 1 With the increase of laser energy, the relative expression of miR-206 increased. The relative expression of miR-206 in the high-energy laser irradiated group was 2.01 ( Figure 5C).…”
Section: Effect Of Laser Irradiation On the Expression Of Mir-206 Amentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that TGFB2‐OT1 is involved in the negative regulation of apoptosis and positive regulation of autophagy and inflammation in vascular endothelial cells . Long Xiang Tu and colleagues reported the up‐regulation of TGFB2‐OT1 in fibroblasts derived from hypertrophic scars, suggesting its involvement in excessive proliferation of fibroblasts and accumulation of extracellular matrix . As concerns TGFB2, its pro‐fibrogenic role and/or its increased gene or protein expression has been reported in lens fibrosis, kidney fibrosis, cardiac fibrosis and liver fibrosis …”
Section: Discussionmentioning
confidence: 99%
“…31,44 Long Xiang Tu and colleagues reported the up-regulation of TGFB2-OT1 in fibroblasts derived from hypertrophic scars, suggesting its involvement in excessive proliferation of fibroblasts and accumulation of extracellular matrix. 45 As concerns TGFB2, its pro-fibrogenic role and/or its increased gene or protein expression has been reported in lens fibrosis, kidney fibrosis, cardiac fibrosis and liver fibrosis. 46 Several studies reported the involvement of BNIP3L in the regulation of pathways associated with NASH pathogenesis, specifically, apoptosis, necrosis, autophagy and fibrosis.…”
Section: Discussionmentioning
confidence: 99%